Interventions to reduce the incidence of surgical site infection in colorectal resections: systematic review with multicomponent network meta-analysis (INTRISSI): study protocol - Friedrichs, Juliane; Seide, Svenja; Vey, Johannes; Zimmermann, Samuel; Hardt, Julia; Kleeff, Jörg H.; Klose, Johannes; Michalski, Christoph; Kieser, Meinhard; Pilz, Maximilian; Ronellenfitsch, Ulrich (BMJ open, 2021)
Objective: To assess the relative contribution of intravenous antibiotic prophylaxis, mechanical bowel preparation, oral antibiotic prophylaxis, and combinations thereof towards the reduction of surgical site infection (SSI) incidence in elective colorectal resections. Methods and analysis: A systematic search of randomised controlled trials comparing interventions to reduce SSI incidence will be conducted with predefined search terms in the following databases: MEDLINE, LILACS, Cochrane Central Register of Controlled Trials (CENTRAL) and the Cochrane Database of Systematic Reviews (CDSR). Additionally, several online databases will be searched for ongoing trials, and conference proceedings and reference lists of retrieved articles will be hand searched. The title-abstract screening will be partly performed by means of a semiautomated supervised machine learning approach, which will be trained on a subset of the identified titles and abstracts identified through traditional screening methods. The primary analysis will be a multicomponent network meta-analysis, as we expect to identify studies that investigate combinations of interventions (eg, mechanical bowel preparation combined with oral antibiotics) as well as studies that focus on individual components (mechanical bowel preparation or oral antibiotics). By means of a multicomponent network meta-analysis, we aim at estimating the effects of the separate components along the effects of the observed combinations. To account for between-trial heterogeneity, a random-effect approach will be combined with inverse variance weighting for estimation of the treatment effects. Associated 95% CIs will be calculated as well as the ranking for each component in the network using P scores. Results will be visualised by network graphics and forest plots of the overall pairwise effect estimates. Comparison-adjusted funnel plots will be used to assess publication bias. Ethics and dissemination: Ethical approval by the Ethical Committee of the Medical Faculty of the Martin-Luther-University Halle-Wittenberg (ID of approval: 2021-148). Results shall be disseminated directly to decision-makers (eg, surgeons, gastroenterologists, wound care specialists) by means of publication in peer-reviewed journals, presentation at conferences and through the media (eg, radio, TV, etc). PROSPERO registration number: CRD42021267322.
Gesehen am 12.01.2022